2008
DOI: 10.1098/rspb.2007.1494
|View full text |Cite
|
Sign up to set email alerts
|

Neotyphodiumendophyte infection frequency in annual grass populations: relative importance of mutualism and transmission efficiency

Abstract: Persistence and ubiquity of vertically transmitted Neotyphodium endophytes in grass populations is puzzling because infected plants do not consistently exhibit increased fitness. Using an annual grass population model, we show that the problems for matching endophyte infection and mutualism are likely to arise from difficulties in detecting small mutualistic effects, variability in endophyte transmission efficiency and an apparent prevalence of non-equilibrium in the dynamics of infection. Although endophytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
154
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(159 citation statements)
references
References 38 publications
(106 reference statements)
5
154
0
Order By: Relevance
“…Variation in vertical transmission efficiency is thought to be an important driver of endophyte dynamics and equilibrium prevalence, as the 'benefit' from endophyte infection is relatively weak (Afkhami and Rudgers, 2008;Gundel et al, 2008). However, although loss in seed storage argues for a role of temperature in endophyte dynamics, exploration of the whole transmission cycle under natural conditions is required to determine the sensitivity of endophyte dynamics to thermal environment: loss of endophyte infection can occur at any of three stages-from tiller to seed, seed to seedling and during tiller growth (Afkhami and Rudgers, 2008).…”
Section: Physiological Cost Of Symbionts At Different Temperaturesmentioning
confidence: 99%
“…Variation in vertical transmission efficiency is thought to be an important driver of endophyte dynamics and equilibrium prevalence, as the 'benefit' from endophyte infection is relatively weak (Afkhami and Rudgers, 2008;Gundel et al, 2008). However, although loss in seed storage argues for a role of temperature in endophyte dynamics, exploration of the whole transmission cycle under natural conditions is required to determine the sensitivity of endophyte dynamics to thermal environment: loss of endophyte infection can occur at any of three stages-from tiller to seed, seed to seedling and during tiller growth (Afkhami and Rudgers, 2008).…”
Section: Physiological Cost Of Symbionts At Different Temperaturesmentioning
confidence: 99%
“…Theoretical models show that imperfect transmission can stabilize intermediate infection frequencies, even when symbionts confer a strong fitness advantage, because there is a persistent source of nonsymbiotic hosts each generation (Turelli 1994;Ravel et al 1997;Gundel et al 2008). Empirical studies have confirmed that imperfect symbiont transmission is widespread in plant and animal hosts (e.g., Hurst et al 2001;Moran and Dunbar 2006;Afkhami and Rudgers 2008;Gundel et al 2011) and contributes to intermediate symbiont frequencies in natural populations (Gibert and Hazard 2013;Yule et al 2013).…”
Section: Introductionmentioning
confidence: 91%
“…Counterintuitively, strong host-symbiont mutualism may actually facilitate persistence of symbiont-free hosts if it is also associated with niche differentiation. Imperfect transmission (Gundel et al 2008) and migration (Saikkonen et al 2002) could further cloud connections between fitness effects of symbionts and local symbiont frequency, as others have recognized (Cheplick and Faeth 2009), and modeling their influence can provide additional insights. Thus, observed symbiont frequencies are, at best, incomplete information about the fitness effects of symbionts on hosts and, at worst, completely mute on the issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations